Experiments on the kerf quality characteristic of mild steel while cutting with a high-power fiber laser. (October 2022) - Liu, Yanjie; Zhang, Shijin; Zhao, Yue; Ren, Ziwei
Graphical abstract: Highlights: High-power fiber laser was feasible to cut 25 mm thick mild steel plate with high efficiency. The effect of process parameters on the kerf taper were analyzed. The effect of line energy on the kerf taper was analyzed. The kerf taper's model was established with regression analysis. The formation mechanism of the kerf taper was studied. Abstract: The laser cutting capacity has increased significantly in recent years, owing to the rising power of fiber lasers. Meanwhile, considerable emphasis is being paid to the quality of high-power laser cutting, particularly the issue of thick plate kerf taper. However, the mechanism by which the kerf taper is formed and the effect of process parameters on the kerf taper are rarely examined in detail when cutting a thick plate with a high-power fiber laser. The purpose of this study is to conduct a series of cutting tests using a 12-kW continuous-wave multimode ytterbium-doped fiber laser. The single factor experiment approach is utilized to determine the effect of each process parameter (stand-off distance, cutting speed, defocus amount, and auxiliary gas pressure) on the kerf taper of 25 mm thick mild steel. The Taguchi method of L25 orthogonal array is used to design the laser cutting experiment, and analysis of variance was used to determine the significant factor impacting the kerf taper. The regression model for the kerf taper was created using the experimental data. Further, the experimental study was used to analyze the mechanism by which the kerf taper of the thick plate was formed.